The MIS 13 interglacial at Ceprano, Italy, in the context of Middle Pleistocene vegetation changes in southern Europe. (1st November 2018) - Margari, V.; Roucoux, K.; Magri, D.; Manzi, G.; Tzedakis, P.C.
Abstract: Climatic and environmental changes of the Middle Pleistocene in Europe provide the context for an important phase in the evolution and dispersal of early hominins. Pollen records from terrestrial and marine sediment sequences reveal patterns not usually visible in palaeoenvironmental reconstructions from archaeological sites alone and show that hominin evolution took place against a background of marked environmental change as forests expanded and contracted in concert with global and regional climatic shifts. It is rare to find archaeological material in stratigraphically long and continuous palaeoenvironmental sequences, yet this is what is needed to enable particular phases of hominin evolution to be securely associated with climatic and environmental changes. At the well-known Middle Pleistocene archaeological site of Ceprano in Italy we have been able to produce a pollen record from the sedimentary unit directly below the stratum of the hominin remains. The new pollen data from Ceprano are presented here in full for the first time and provide a detailed picture of interglacial vegetation development during Marine Isotope Stage (MIS) 13. This evidence contributes significantly to our knowledge of the spatial heterogeneity of ecosystem responses to climatic change during this period and helps to further constrain the age of the hominin remains. New sites combining both archaeology and long, continuous high quality palaeoecological records would help clarify the relationship between hominin presence and palaeoclimatic and palaeoenvironmental conditions. In the meantime, better communication between the research communities can also go a long way to improving our understanding of the links between the two. Highlights: The paper presents the detailed palynological record from the early hominin site of Ceprano in central Italy. An extensive review of central Italian Middle Pleistocene sites places the record in context. A wider review of southern European Middle Pleistocene records provides the environmental background to hominin evolution.